Regiospecific Cation Exchange in Nanocrystals and Its Potential in Diversifying the Nanostructural Library. Issue 1 (3rd December 2022) - Hong, Yongju; Venkateshalu, Sandhya; Jeong, Sangyeon; Park, Jongsik; Lee, Kwangyeol
Abstract : The cation‐exchange reaction (CER), a promising nanocrystal (NC) engineering strategy, has undergone rapid progress in the past decade, sparking a big wave of interest in the post‐synthetic tuning of chemical compositions, crystal phases, interfaces, morphologies, and corresponding properties. However, a significant gap has existed between the theoretical and actual CERs, hindering the popularization of CERs for explosive expansion in NC designs. A notable roadblock in this area has been the inability to control the site of cation exchange within the nanostructure, although partial cation exchange at desired sites can open an avenue to the vast structural diversity of nanostructures and accompany new physicochemical properties. Several notable successes have been recorded recently in fabricating predesigned hetero‐nanostructures by thoroughly understanding the principles of cation exchange and by exploiting the peculiarity of each crystal system. Herein, recent advances achieved in the CER are introduced, unraveling the critical factors controlling regiospecificity by analyzing the developed theories and accumulated experimental results. It is further described how this knowledge can be harnessed to design advanced NCs, and the beneficial effect of regiospecificity on material properties is highlighted. Finally, the challenges and research directions are provided to encourage further research in this burgeoning field. Abstract : Current challenges in cation‐engineered nanocrystals (NCs) have been addressed, emphasizing the importance of regiospecificity control during cation‐exchange reactions. In particular, a comprehensive list of studies on regiospecificity‐engineered hetero‐nanostructures is detailed, primarily focused on improving corresponding physicochemical properties, and the favorable effects of the geometrics are systematically organized based on the structures of NCs.